Inversión Extranjera Directa y su efecto sobre la desigualdad para 80 países del mundo, un análisis con técnicas econométricas actuales de datos de panel, periodo 1980-2016 - Garrochamba Sánchez, Víctor Andrey (2019)
The growing inequality represents one of the main economic and social problems of the current world economy, which, thanks to globalization, has been modified by the free movement of capital that goes from one country to another in the form of Foreign Direct Investment (FDI) as well. that every time resources are concentrated in fewer people even though population growth does not stop. Therefore, the research work has as a general objective to determine the relationship between FDI and inequality for 80 countries of the world classified by income groups, in the period of 1980 - 2016 to analyze its causality through the application of economic techniques to current panel data. Data were obtained from the World Bank database (2017) for this research. To determine the balance, the Pedroni (1999) cointegration tests for the long term and Westerlum (2007) and the Dumitresco and Hurlin (2012) causality test based on the Granger type (1988) were applied. He found that FDI has a positive and significant effect on inequality at the global level, high-income countries and low-income countries, while in the middle and low-middle-income countries the effect is negative. Together and by groups of countries by income there is a long and short term balance between the variables. Once the causality test was applied, it was obtained in the high-income countries unidirectional causality of direct foreign investment towards inequality and in low-income countries unidirectional causality of inequality towards direct foreign investment.